2016
DOI: 10.1186/s40064-016-2194-5
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme complex increases in vitro dry matter digestibility of corn and wheat in pigs

Abstract: Two experiments were conducted to determine the effects of enzyme complex on in vitro dry matter (DM) digestibility for feed ingredients. The objective of experiment 1 was to screen feed ingredients that can be effective substrates for an enzyme complex, mainly consisted of β-pentosanase, β-glucanase and α-amylase, using in vitro digestibility methods. In experiment 1, the test ingredients were three grain sources (barley, corn and wheat) and six protein supplements (canola meal, copra expellers, cottonseed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
(26 reference statements)
4
15
1
Order By: Relevance
“…The analytical markers for such arabinoxylans are high arabinose/xylose and uronic acid/xylose ratios (Pedersen et al, 2014). The bulk of any in vitro enzymatic digestibility of maize fibre could be starch, and not the hull iNSP (Park et al, 2016a). Unlike the extremely diverse pig gut microbial enzyme activities, only limited activities are expressed in manufactured enzyme cocktails.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical markers for such arabinoxylans are high arabinose/xylose and uronic acid/xylose ratios (Pedersen et al, 2014). The bulk of any in vitro enzymatic digestibility of maize fibre could be starch, and not the hull iNSP (Park et al, 2016a). Unlike the extremely diverse pig gut microbial enzyme activities, only limited activities are expressed in manufactured enzyme cocktails.…”
Section: Discussionmentioning
confidence: 99%
“…The best insight into the underpinning mechanics might be through a modelling approach (Zijilstra et al, 2010). Modelling in turn requires potent methods to mimic porcine fibre digestion for robust prediction of the biogenic effects (Lee at al., 2018), and to match enzymes to dietary NSP (Park et al, 2016a). Effective methods should be standardised, low cost, rapid and broadly applicable across a range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Pang and Applegate (2007) reported that the in vitro solubility of Cu might not accurately represent the bioavailability of Cu in broilers. Although it is impossible to exactly mimic the in vivo digestion in the in vitro digestion assay due to the physiological and environmental factors (Boisen and Eggum, 1991), the in vitro digestion procedure has been employed in the evaluation of feed ingredients (Park et al, 2012; Cervantes-Pahm et al, 2013), exogenous enzyme tests (Kong et al, 2015; Park et al, 2016), and mycotoxin sequestering agents (Kong et al, 2014). In the present work, as all Cu sources were dissolved in the solutions prepared to simulate the digestive tract of pigs, the solubility of Cu determined in the in vitro digestion assay for pigs may represent the bioavailability of Cu in Cu sources for pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro digestion assays were based on the in vitro digestion technique (Boisen and Fernández, 1997;Park et al, 2016). All IVDMD procedures were conducted in triplicate.…”
Section: In Vitro Disappearance Assaysmentioning
confidence: 99%
“…In vitro assays are widely used to determine the influences of enzyme supplementation on nutrient digestibility because in vitro assay data are very highly correlated with data obtained from animal experiments (Park et al, 2012). In addition, an in vitro assay is a time-saving and inexpensive method compared with in vivo experiments (Kong et al, 2015;Park et al, 2016). Therefore, the objectives of this study were to determine In Vitro Dry Matter Disappearance (IVDMD) in two sources of BDG from different countries and corn distillers dried grains with solubles (DDGS) and to investigate effects of supplemental β-glucanase on the IVDMD in barley, BDG and corn DDGS.…”
Section: Introductionmentioning
confidence: 99%